2018
DOI: 10.4067/s0718-58392018000300339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rhamnogalacturonan I fragments as elicitors of the defense mechanism in tomato fruit

Abstract: The rhamnogalacturonan I (RGI) is part of pectin plant cell wall, and currently there is scarce information about the elicitor effect of its fragments in the fruit defense mechanism. In this work, the effect of the fragments of RGI on the defense mechanism in tomato (Solanum lycopersicum L.) fruits was evaluated. Three fragments of RGI released from enzymatic degradation by RG lyase were characterized according to their physical-chemical and structural characteristics. Two of RGI fragments (F-1 and F-2) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The findings of that research concluded that Solyc04g076660 and Solyc04g076630 genes are involved in the early stages of tomato fruit development in which it is growing mainly by cell expansion and the Solyc11g011300 gene plays a role in the fruit softening phenomena during tomato fruit ripening. Furthermore, Jiménez-Maldonado et al (2018) assessed the effect of RG-I fragments from potato on the defense mechanism in tomato fruits. Two fragments of RG-I with a molecular weight of 20 and 16 kDa (F-1 and F-2 fragments respectively) induced the enzymatic activity of β-1,3-glucanase at 6 h after treatment.…”
Section: Role Of Rgl Genes In Plant Physiologymentioning
confidence: 99%
“…The findings of that research concluded that Solyc04g076660 and Solyc04g076630 genes are involved in the early stages of tomato fruit development in which it is growing mainly by cell expansion and the Solyc11g011300 gene plays a role in the fruit softening phenomena during tomato fruit ripening. Furthermore, Jiménez-Maldonado et al (2018) assessed the effect of RG-I fragments from potato on the defense mechanism in tomato fruits. Two fragments of RG-I with a molecular weight of 20 and 16 kDa (F-1 and F-2 fragments respectively) induced the enzymatic activity of β-1,3-glucanase at 6 h after treatment.…”
Section: Role Of Rgl Genes In Plant Physiologymentioning
confidence: 99%
“…The activity of the RGL enzyme has been reported to be involved in cell wall enlargement by changing the cohesion network in cotton cotyledons (Gossypium hirsutum L.) (Naran et al, 2007), the activation of the defense system in tomato (Jiménez-Maldonado et al, 2018), the regulation of cell division and periderm development (Oomen et al, 2002) and the control of cell wall architecture in potato (Solanum tuberosum) (Huang et al, 2017). Recently, it was reported that RGL isoenzymes are involved in the deposition of tertiary cell wall fibers in flax (Linum usitatissimum) (Mokshina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%